ANALISIS MANAJEMEN RANTAI PASOK (Supply Chain) INDUSTRI SAGU KABUPATEN KEPULAUAN MERANTI (Studi Kasus PT. Nasional Sago Prima) - Meki Herlon; Riska Dian Oktari; Khairunnas Khairunnas; Zulhamid Ridho (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The research objective was to analyze the supply chain of the sago industry in the Meranti Islands Regency. Case Study PT. Nasional Sago Prima (PT. NSP). The research was carried out in March - October 2020. The research method was a survey. The analysis used: qualitative and quantitative. Qualitative analysis to describe the mechanism and flow pattern of the supply chain for the sago industry. Meanwhile, quantitative analysis is used to analyze components and supply chain activities. The results showed: 1). The supply chain mechanism for the sago industry that occurs is the creation of collaboration and coordination between supply chain actors from upstream to downstream. The flow pattern of the supply chain, which consists of raw material flow, product flow, financial flow and information flow, went smoothly. 2). The resistance of the supply chain for the sago flour industry are: A). 70% of the raw material for sago tual is supplied from outside the company, because the nucleus plantations have not yet entered the full harvest period. B). Inefficient processing costs due to: the cost of using electricity and the high cost of water filtration processes.